A Study of the Relationship between Body Mass Index and Menstrual Cycle Disturbances - شنيعة, لميس; جهاد الأيوب; سحر حسن (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The objective of this research is to study the prevalence of menstrual cycle disorders and to assess the relationship between body mass index and menstrual cycle disorders. Patients and methods: Observational Descriptive study(cross-sectional) was involved 392 patients visited gynecological clinic at Tishreen university hospital in Latakia investigated for inclusion criteria. It was included women aged (20-40) years didn't have abvious causes for menstrual cycle disorders. A detailed clinical history was taken and a clinical examination included measuring weight and height to determine BMI. According to the values, the division was into four groups. A menstrual history was taken (menarche, LMP, regularity of menstruation). The patients were divided according to the possible patterns of menstrual cycle disorders. Ultrasound evaluation of the reproductive system was performed. The duration of the research is a full year from March 2021 to March 2022 AD. Results: The current study showed that 6.9% of the sample were underweight, 39.3% normal weight, 32.9% overweight and 20.9% obese. 21.2% had normal menstruation and 78.8% had irregular menstruation. We found that there is a statistically significant correlation (P=0.005) between the high percentage of menstrual cycle disorders and abnormal BMI values. The percentage of amenorrhea and polymenorrhea was higher among obese women, followed by underweight and the difference between groups was statistically significant (P=0.04),(P=0.02). Oligomenorrhea was found in higher percentage among overweight women followed by obese and the difference between groups was statistically significant (P=0.001). The percentage of menorrhagia was higher among obese women followed by overweight then underweight. And the the difference between groups was statistically significant (P=0.04). Dysmenorrhea was higher in underweight women followed by obese then in equal proportion among overweight and normal weight with statistically significant difference (P=0.003). There was no statistically significant difference between the groups for hypomenorrhea (P=0.5), intermenstrual bleeding (P=0.1) and menorrhagia (P=0.09). Conclusion: Menstrual cycle disorders during the reproductive ages are common. BMI plays a very important role for regulating menstrual cycle. weight control is important for improving a woman’s quality of life during her reproductive years.